Contribution to the perception of the social structure of a town in the case of the town Lenart v Slovenskih goricah - Drozg, Vladimir (Journal for Geography, 2016)
The social structure of a town illustrates the layout of elements and features with social content. It is usually presented with social indicators of the population of a said town; that is by age, ethical and religious affiliation, education, economic circumstances and similar social characteristics. Characteristics of such impressions means that they are made on the basics of statistical data and according to the domicile principle. However, the city is a dynamic formation; it cannot be explored just by taking into account the place of residence of the population. In social geography and urban sociology there is the realization, that members of the same or similar social characteristics are territorially and functionally interconnected. Functional interconnection means that they work and act (thus “operate”) together, in a similar way, at the same locations and at the same time. The word “operate” refers to the satisfaction of the basic human needs, such as living, working, care and provisions, education, recreation and communication. Functional interconnection therefore relates to similar habits regarding supply of provisions at the same locations, going to the same or similar stores, similar recreation habits, and usage of same or similar recreational areas and so on. This creates emerging areas (in large cities) or individual objects (in small towns) which are frequented by people of specific social characteristics. This social sediment can be seen in the function, form, and position within the city, perhaps even in size. The paper shows the results of social structure of a small town based on the places, where specific social groups satisfy their needs.
Keywords: social geography; urban geography; place; social group; Lenart